Screen or whiteboard: comparative analysis of academic performance and satisfaction in learning English for Specific Purposes (ESP) in the health area - Alfaro Salas, Hazel (2025)
This study compared the impact of virtual and in-person modalities on the academic performance and satisfaction of 29 ESP health students at a university in Costa Rica. Using a non-experimental quantitative design, information was collected through questionnaires and records of grades, academic status, and absences. The results show that the in-person modality offers greater stability and consistency in grades and fewer withdrawals, while the virtual modality presents greater dispersion in grades and challenges such as lack of active participation and isolation. The in-person modality provides a more enriching experience due to direct interaction, while the virtual modality stands out for its flexibility and access to educational resources. Combining both approaches could optimize the educational experience